HPV sensitizes OPSCC cells to cisplatin-induced apoptosis by inhibiting autophagy through E7-mediated degradation of AMBRA1. Issue 10 (3rd October 2021) - Antonioli, Manuela; Pagni, Benedetta; Vescovo, Tiziana; Ellis, Rob; Cosway, Benjamin; Rollo, Francesca; Bordoni, Veronica; Agrati, Chiara; Labus, Marie; Covello, Renato; Benevolo, Maria; Ippolito, Giuseppe; et al.
ABSTRACT: Oropharyngeal squamous cell carcinoma (OPSCC) is an increasing world health problem with a more favorable prognosis for patients with human papillomavirus (HPV)-positive tumors compared to those with HPV-negative OPSCC. How HPV confers a less aggressive phenotype, however, remains undefined. We demonstrated that HPV-positive OPSCC cells display reduced macroautophagy/autophagy activity, mediated by the ability of HPV-E7 to interact with AMBRA1, to compete with its binding to BECN1 and to trigger its calpain-dependent degradation. Moreover, we have shown that AMBRA1 downregulation and pharmacological inhibition of autophagy sensitized HPV-negative OPSCC cells to the cytotoxic effects of cisplatin. Importantly, semi-quantitative immunohistochemical analysis in primary OPSCCs confirmed that AMBRA1 expression is reduced in HPV-positive compared to HPV-negative tumors. Collectively, these data identify AMBRA1 as a key target of HPV to impair autophagy and propose the targeting of autophagy as a viable therapeutic strategy to improve treatment response of HPV-negative OPSCC. Abbreviations : AMBRA1: autophagy and beclin 1 regulator 1; CDDP: cisplatin (CDDP); FFPE: formalin-fixed paraffin-embedded (FFPE); HNC: head and neck cancers (HNC); HPV: human papillomavirus (HPV); hrHPV: high risk human papillomavirus (hrHPV); OCSCC: oral cavity squamous carcinomas (OCSSC); OPSCC: oropharyngeal squamous cell carcinoma (OPSCC); OS: overall survival (OS); qPCR: quantitative polymerase chain reaction; RB1: RB transcriptional corepressor 1; ROC: receiver operating characteristic curve (ROC).